2005
DOI: 10.3354/dao067239
|View full text |Cite
|
Sign up to set email alerts
|

Changes in epizoic crustacean infestations during cetacean die-offs: the mass mortality of Mediterranean striped dolphins Stenella coeruleoalba revisited

Abstract: In the summer and autumn of 1990, a cetacean morbillivirus caused a massive epizootic mortality of striped dolphins Stenella coeruleoalba in the western Mediterranean. Previous circumstantial evidence suggested that the disease could also have increased host susceptibility to infestations with epizoic crustaceans. In this study we provide strong evidence supporting this hypothesis. We examined striped dolphins stranded along the Mediterranean central coast of Spain from 1981Spain from to 2004, and recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…The Stenella coeruleoalba that succumbed to the 1990-1992 epidemic were in a poor nutritional state, with lipid reserves estimated to be only about 60% of usual values for this population, an energy depletion that could not be explained by the effect of the disease alone (Aguilar & Raga 1993). Also, the prevalence of ectoparasites and epibionts was much higher than reference values for this population, suggesting that during the epidemic more dolphins were susceptible to infestations, possibly because they were immunodepressed by the disease and were suffering from behavioural alterations such as reduced swimming speed (Aguilar & Raga 1993, Aznar et al 2005. The abnormally high sea-surface temperatures (SSTs) and low rainfall conditions in the winter preceding the 1990-1992 outbreak in the western Mediterranean apparently depressed peak productivity that occurs each year in early spring and determines the regional abundance of fish (Aguilar & Raga 1993).…”
Section: Cetacean Morbillivirusmentioning
confidence: 99%
“…The Stenella coeruleoalba that succumbed to the 1990-1992 epidemic were in a poor nutritional state, with lipid reserves estimated to be only about 60% of usual values for this population, an energy depletion that could not be explained by the effect of the disease alone (Aguilar & Raga 1993). Also, the prevalence of ectoparasites and epibionts was much higher than reference values for this population, suggesting that during the epidemic more dolphins were susceptible to infestations, possibly because they were immunodepressed by the disease and were suffering from behavioural alterations such as reduced swimming speed (Aguilar & Raga 1993, Aznar et al 2005. The abnormally high sea-surface temperatures (SSTs) and low rainfall conditions in the winter preceding the 1990-1992 outbreak in the western Mediterranean apparently depressed peak productivity that occurs each year in early spring and determines the regional abundance of fish (Aguilar & Raga 1993).…”
Section: Cetacean Morbillivirusmentioning
confidence: 99%
“…Other indices of inbreeding (internal relatedness) or population bottlenecks did not show further evidence for low genetic diversity. Since previous research showed that inbreeding affects the health status of cetaceans (Aznar et al, 2005;Dove, 2009), it would be interesting to test for a link between health or cause of death and individual genetic diversity when larger datasets become available.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent organic pollutants (POPs) such as polychlorinated biphenyls (PCBs) are present at high concentrations (1200 mg/ g) in some areas within the Great Lakes (Cieniawski and Collier 2003;Hornbuckle et al 2006). PCBs are known to elicit a myriad of toxic effects ranging from immunosuppression to cancer (Silkworth and Antrim 1985;Aznar et al 2005). Lipidrich Diporeia would be an ideal target for lipophilic-PCB mediated toxicity, which could potentially increase the susceptibility of Diporeia to secondary stressors (e.g., pathogens; Landrum et al , 2001.…”
Section: Introductionmentioning
confidence: 99%